Mobile Travel Apps Engagement: Measuring Tourists’ Perception - Imtiaz, Humera; Mohd Suki, Norazah (International Journal of Interactive Mobile Technologies (iJIM), 2022)
Mobile travel apps have revolutionised the way people book flights, hotels, and excursions, as well as how travel firms contact clients. This study examines tourists’ perception of mobile travel apps engagement in Pakistan. A field intercept survey was distributed to 500 respondents approached at tourism sites with a high flow of tourists in Northern Pakistan. Data were analyzed using exploratory factor analysis (EFA) via the Statistical Package for Social Sciences (SPSS) version 23 and conﬁrmatory factor analysis (CFA) the Partial Least Square-Structural Equation Modeling (PLS-SEM) approach using Smart-PLS 3.0 software. The EFA analysis by using the principal component method of extraction and the varimax method of rotation yielded five factors. Respondents heavily emphasize item TS2 “I am very satisfied with the mobile travel apps” of tourist satisfaction factor. Likewise, this item emerged as the most dominant in the CFA analysis, followed by item TS3 "I am happy with the mobile travel apps", and item TS4 "I am satisfied with the way mobile travel app organizes the trip". The findings are vital to advancing extant mobile travel apps engagement research, while also guiding their developers to better design mobile travel apps to boost tourists’ trust and satisfaction. Direction for further research is furnished.